Differential age‐specific distribution of influenza virus types and subtypes in tropical Singapore, 2011 to 2017. Issue 8 (9th April 2019) - Ang, Li Wei; Cui, Lin; Mak, Tze Minn; Ng, Yixiang; Leo, Yee Sin; Lee, Vernon Jian Ming; Lin, Raymond Tzer‐Pin
Abstract: Surveillance and reporting of epidemiological features of seasonal influenza mostly are aggregates across all‐ages. We investigated age‐specific differences in distribution of influenza virus (sub)types in tropical Singapore, using laboratory‐confirmed virological data collected under the national influenza surveillance programme from 2011 to 2017. The proportion of influenza‐positive specimens from outpatients with influenza‐like illness was used as an indicator of influenza activity in the community. The highest influenza positivity for age groups of 5 to 14 years and 15 to 64 years coincided in the same month in 5 out of the 7 years under study. Influenza positivity was lowest in young children <5 years of age compared with older age groups. Influenza A(H3N2) was most prevalent in the community except in 2012 when a predominance of influenza B was observed. The dominant virus (sub)type varied across the years in children <5 years and 5 to 14 years of age. Influenza A(H3N2) was the predominant circulating virus subtype among elderly persons aged ≥65 years during the 7‐year period, and among adults aged 15 to 64 years since 2013. Knowledge about the age‐specific differences in distribution of influenza virus (sub)types helps to facilitate better understanding of seasonal epidemics and to inform targeted strategies in prevention and control of influenza virus transmission. Highlight: Influenza peak for age groups of 5–14 years and 15–64 years mostly coincided in the same month. Influenza positivity was lowest in young children <5 years of age. Children <5 years of age experienced a mixture of influenza A and B viruses as the predominant types. Age groups of 5–14 years and 15–64 years were mostly affected by A(H3N2) followed by influenza B. Influenza A(H3N2) was particularly prevalent in elderly persons aged ≥65 years.